EFEKTIVITAS PROBLEM-BASED LEARNING TERHADAP KETERAMPILAN ARGUMENTASI MAHASISWA TENTANG ISU SOSIOSAINTIFIK LINGKUNGAN - rita istiana; Desti Herawati; Nadiroh Nadiroh; Putu Ronny Angga Mahendra (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
THE EFFECTIVENESS OF PROBLEM-BASED LEARNING AGAINST STUDENT ARGUMENTATION SKILLS ABOUT ENVIRONMENTAL SOCIOCULTURAL ISSUESAbstractThe low quality of argumentation made by students is caused by the learning process, which is generally in the form of knowledge transfer only. Students are rarely allowed to investigate an issue and develop the ability to reason, think critically, and submit arguments about environmental issues. Teaching socio-scientific issues can have a positive influence on student motivation, contribute to student learning outcomes, develop critical thinking skills, decision-making skills, argumentation skills, and moral development. The purpose of this study is to improve students' argumentation skills on environmental socio-scientific issues through the application of problem-based learning models. Also, to analyze the effectiveness of models problem-based learning in improving students' argumentation skills on socio-scientific environmental problems. The research was conducted at the Biology Education Study Program, Faculty of Teacher Training and Education, Pakuan University, from January 2018 to August 2018. The research period was an even semester of the 2017/2018 school year. The subjects of this study were the Biology Education Study Program students in semester V. Research methods used in this research is Experimentation. The instrument used is through expert judgment. Increasing the argumentation skills of prospective biology teacher candidates in lectures using the model is Problem based Learning still shallow. A very slight increase in N-Gain marks this. All students can submit arguments with the reasons on which they are provided. However, most of the arguments put forward have data/evidence that is invalid and irrelevant and, therefore, unable to corroborate the arguments submitted. Keywords: Argumentation Skills; Problem Based Learning; Socio-scientific IssuesAbstrakRendahnya kualitas argumentasi pada mahasiswa disebabkan oleh proses pembelajaran yang pada umumnya berupa transfer pengetahuan. Mahasiswa jarang diberi kesempatan untuk menyelidiki sebuah isu dan mengembangkan kemampuan bernalar, berpikir kritis, dan mengajukan argumen mengenai isu-isu lingkungan. Pengajaran isu sosiosaintifik dapat menimbulkan pengaruh positif terhadap motivasi peserta didik, berkontribusi terhadap hasil belajar peserta didik, mengembangkan keterampilan berpikir kritis, keterampilan membuat keputusan, keterampilan argumentasi, dan perkembangan moral. Tujuan dari penelitian ini untuk meningkatkan keterampilan argumentasi mahasiswa mengenai isu sosiosaintifik lingkungan melalui penerapan model pembelajaran problem-based learning dan menganalisis efektivitas model pembelajaran problem-based learning dalam meningkatkan keterampilan argumentasi mahasiswa mengenai isu sosiosaintifik lingkungan. Penelitian dilaksanakan di Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pakuan, pada bulan Januari 2018 sampai Agustus 2018. Waktu penelitian adalah semester genap tahun ajaran 2017/ 2018. Subjek penelitian ini adalah mahasiswa Program Studi Pendidikan Biologi semester V. Metode penelitian yang digunakan dalam penelitian ini adalah Eksperimen. Instrumen yang digunakan melalui expert judgment. Peningkatan keterampilan argumentasi mahasiswa calon guru biologi dalam perkuliahan dengan model Problem based Learning masih sangat rendah. Hal ini ditandai dengan kenaikan N-Gain yang sangat sedikit. Semua mahasiswa sudah mampu mengajukan argumen dengan alasan yang menjadi dasar pengajuan. Namun, sebagian besar argumen yang diajukan memiliki data/ bukti yang tidak valid dan tidak relevan sehingga tidak mampu menguatkan argumen yang diajukan.Kata Kunci: Ketrampilan Argumentasi; Problem Based Learning; Isu sosiosaintifik